Modelling climate influences on population dynamics and diurnal time budget of the Shelduck (Tadorna tadorna) wintering in Ramsar wetlands of Algeria. Issue 3 (August 2019) - Bezzalla, Adel; Houhamdi, Moussa; Cherif Maazi, Mohamed; Chenchouni, Haroun
Several North African wetlands are classified as wetlands of international importance (Ramsar sites and Important Bird Area) because thousands of Shelducks ( Tadorna tadorna ) winter in these habitats. However, Shelduck's patterns of habitat use in these protected wetlands during the wintering season are still hindered by lack of information in arid and semi-arid regions regarding population dynamics and the effects of climate variables. This ornithological survey aims to study population dynamics and temporal patterns of diurnal activities of the Shelduck at two Ramsar and Important Bird Area sites (Chott Tinsilt and Sebkhet Ezzemoul) with respect to the effect of climatic parameters of the habitat in order to deepen our understanding of wintering strategies and habitat use. Populations were weekly censused from 06:00 to 19:00 during the entire wintering season (September 2015–May 2016). Diurnal behavioural activities were monitored at the same rate, and then the variation of time budget was tested using generalized linear model to determine the effects of climate variables and conspecific density dependence. The Shelduck was observed at both sites from the end of November and remained there until the total desiccation of both lakes in early May. Trends of Shelduck's population dynamics differed between the two sites. Generalized linear models revealed the significant effects of temperature, wind speed and number of snowy days on population dynamics. Feeding was the main diurnal activity of the Shelduck at both sites with 80.2% of time budget at Chott Tinsilt (mainly feeding at lake shores) and 82% at Sebkhet Ezzemoul (mainly feeding in water). The generalized linear models showed that the variation of time budget allocated to different diurnal activities was not density-dependent, but rather it was negatively affected by the increase of air temperature. Significant effects of the interaction between population size and some climatic variables were found and discussed. During the whole wintering season, Chott Tinsilt and Sebkhet Ezzemoul play an important ecological role since they offer a wide-ranging diurnal forging habitat and a shelter for thousands of this waterfowl.